To the 90th Birthday of Professor Igor O. Kulik (1935–2019) - Zagoskin, Alexander (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2025)
This Issue of the journal “Fizyka Nyzkykh Temperatur/Low Temperature Physics” is devoted to the memory of Igor Orestovich Kulik, one of the prominent members of the great Kharkiv school of theoretical physics.